2009
DOI: 10.1371/journal.pntd.0000467
|View full text |Cite
|
Sign up to set email alerts
|

High Burden of Impetigo and Scabies in a Tropical Country

Abstract: BackgroundImpetigo and scabies are endemic diseases in many tropical countries; however the epidemiology of these diseases is poorly understood in many areas, particularly in the Pacific.Methodology/Principal FindingsWe conducted three epidemiological studies in 2006 and 2007 to determine the burden of disease due to impetigo and scabies in children in Fiji using simple and easily reproducible methodology. Two studies were performed in primary school children (one study was a cross-sectional study and the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
136
5
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(166 citation statements)
references
References 25 publications
17
136
5
8
Order By: Relevance
“…Impetigo is also an endemic problem in many less-developed countries (41,45), and MRSA is likely to be on the rise in these contexts also (50). In patients with MRSA and S. pyogenes coinfection, finding a single oral agent that is effective, affordable, and easy to use would be a significant advance.…”
Section: Discussionmentioning
confidence: 99%
“…Impetigo is also an endemic problem in many less-developed countries (41,45), and MRSA is likely to be on the rise in these contexts also (50). In patients with MRSA and S. pyogenes coinfection, finding a single oral agent that is effective, affordable, and easy to use would be a significant advance.…”
Section: Discussionmentioning
confidence: 99%
“…In general, impetigo presents as bullous or papular lesions that progress to crusted lesions, without accompanying systemic symptoms, on exposed areas of the body (usually the face or extremities). Recent studies of impetiginous lesions found recovery rates of 29 to 90% and 57 to 81% for Streptococcus pyogenes and S. aureus, respectively (313)(314)(315)(316).…”
Section: For Photos Of Classical S Aureus Sstis)mentioning
confidence: 99%
“…In contrast, it has been accepted for many years that acute rheumatic fever occurs only following GAS pharyngitis; however, this is unlikely to be the case in tropical settings [32]. The greatest prevalence of rheumatic heart disease is found among the indigenous populations of Australia and the Pacific Island nations, where there is a high burden of GAS impetigo [33]. In these populations GAS pharyngitis is rare, and cases of GAS impetigo outnumber throat carriage or infection ninefold [34].…”
Section: Complications Of Scabiesmentioning
confidence: 99%